Blurring the distinction between software design and work practice - Grace, d; Jirotka, M (2009)
As scientific software is made available within grid infrastructures, EUD increasingly becomes an important activity to support because scientists need to retain a significant amount of control over the code they use to develop experimental workflows and computational models. We present preliminary findings from two case studies where project teams modified the software engineering lifecycle through the implementation of a reconceptualised notion of pair programming as a means in which to facilitate EUD.